Indo-European *Gu̯h in Germanic - Witczak, Krzysztof Tomasz (Lingua Posnaniensis, 2013)
Krzysztof Tomasz Witczak. Indo-European *gÁh in Germanic. Lingua Posnaniensis, vol. LIV (2)/2012. The Poznań Society for the Advancement of the Arts and Sciences. PL ISSN 0079-4740, ISBN 978-83-7654-252-2, pp. 83-90. Purpose and method: In my paper I discuss the development of IE. *gÁh in the Germanic languages, using the historical-comparative method. Results: Two regular reflexes of IE. *gÁh in Proto-Germanic (*g and *w) can be explained by the place of the Indo-European accent, e.g. Gmc. *garmaz m. ‘fire dog’ (< IE. *gÁhórmos) vs. Gmc. *warmaz adj. ‘warm, hot’ (< IE. *gÁhormós); Gmc. *dagaz m. ‘day’ (< IE. *dhogÁhós) vs. Gmc. *snaiwaz m. ‘snow’ (< *snóigÁhos m. ‘snow’). Conclusion: The double distribution of IE. *gÁh in Proto-Germanic, which is motivated by the primitive accent, can be described as a rule similar to das Vernersche Gesetz.